Some remarks about the failing state of Mexico in the light of newborn dictatorships - Stępień-Załucka, Beata (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
Modern Mexico is a country that has long ceased to perform its basic competences. This is particularly evident in the area of human rights protection. Decades of action by organized crime groups have led to the establishment of their power in occupied territories and, consequently, to their impunity. The social response to the crime groups’ activities was the creation of areas belonging to a “warlord” in which warlords exercise their own power, unlimited by law.In this context, several questions arise about what is currently the constitutional form of power and what form of power actually exists in Mexico, including how this power is exercised and, finally, what the current practice of human rights protection is. The answers to these questions can be found in the present article.
Keywords: Mexicoʼs form of government; human rights; cartel dictatorship; Mexican problems